The challenge of transformation: Breaking the barriers - W. P. Esterhuyse (South African Journal of Business Management, 2003)
One of the most commonly used concepts in post-apartheid South Africa is undoubtedly the concept `transformation'. In order to strip this concept of its `bewitchments' (Nietzsche; Wittgenstein) a conceptual analysis is made of the meaning and usage of the term. In view of the distinction between first order change and second order change, the need for transformation (ethical and strategic), the resistance against transformation (systemic and individual) and the execution and management of transformation is discussed.
Keywords: 650